Signal characteristics of electroseismic conversion. (9th February 2018) - Peng, Rong; Di, Bangrang; Wei, Jianxin; Ding, Pinbo; Liu, Zichun; Guan, Bingyan; Huang, Shiqi
Abstract: Electric fields applying on the fluid-filled porous materials can induce small relative pore-fluid motions due to electroseismic conversions. In order to characterize the electroseismic propagation phenomena, we have designed an experimental apparatus to acquire the electroseismic (ES) signals. The electroseismic measurements on different samples have been conducted to confirm the origin of the recorded signals. We find that a strong acoustic signal generates around the electrode and affects the identification of ES signals. To further confirm and distinguish the ES signal as well as the acoustic signal around the electrode, we have analyzed records obtained with regular movements of the receiver, the sample and the source. Analysis has been made on the characteristics of the traveltime, polarity and frequency of ES signals. Our results show that the traveltime of ES signal relates to the distance between the rock sample and the receiver, the location of the exciting electrode has little impact on the traveltime. The applied electric field influences the polarity of ES signal, the polarity of ES signal reverses along with the changes of the electric field direction. While it has no polarity effects on the acoustic signal generated around the electrode. The frequency spectrum of ES signal is absolutely different with that of the acoustic signal generated around the electrode. The acoustic signal around the electrode has multiple dominant frequencies which are mainly in low-frequency range without being affected by the frequency of the electric field. The ES signal has only one dominant frequency which closely relates to the frequency of the electric field. The understanding of the signal characteristics on electroseismic conversion can contribute to a better application and interpretation of ES exploration.